2009
DOI: 10.1021/la900929u
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Freezing on Water Repellent Materials

Abstract: Water drops on hydrophobic microtextured materials sit on a mixture of solid and air. In standard superhydrophobic situations, the drop contacts more air than solid, so that we can think of exploiting the insulating properties of this sublayer. We show here that its presence induces a significant delay in freezing, when depositing water on cold solids. If the substrate is slightly tilted, these drops can thus be removed without freezing and without accumulating on the substrate, a property of obvious practical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
275
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(281 citation statements)
references
References 15 publications
4
275
1
1
Order By: Relevance
“…Kulinich and Farzaneh 75 discovered that CAH plays an important role in anti-freezing and a lower CAH normally contribute to a much longer delay of freezing time. 73,75 Compared with superhydrophobic surfaces, superamphiphobic surfaces normally exhibit much lower water CAH ( SA close to 1° 5 or even lower), as documented extensively. 9,25,46,47,60 Therefore, superamphiphobic surfaces are more promising in anti-freezing though the corresponding study in such an application for superamphiphobic surfaces has not yet been reported.…”
Section: Anti-freezingmentioning
confidence: 89%
See 1 more Smart Citation
“…Kulinich and Farzaneh 75 discovered that CAH plays an important role in anti-freezing and a lower CAH normally contribute to a much longer delay of freezing time. 73,75 Compared with superhydrophobic surfaces, superamphiphobic surfaces normally exhibit much lower water CAH ( SA close to 1° 5 or even lower), as documented extensively. 9,25,46,47,60 Therefore, superamphiphobic surfaces are more promising in anti-freezing though the corresponding study in such an application for superamphiphobic surfaces has not yet been reported.…”
Section: Anti-freezingmentioning
confidence: 89%
“…Surface superhydrophobic modification shows great potential 75 to address such a challenge. Qué ré et al 73 demonstrated that freezing could remarkably be delayed when water droplets were deposited on cold superhydrophobic surfaces. It was reported that the presence of microtextures dramatically delay the freezing time of the water drops, by a factor between 3 and 5.…”
Section: Anti-freezingmentioning
confidence: 99%
“…71 Even surfaces that do not reduce adhesion of ice can depress the nucleation point significantly by increasing the free energy of nucleation. 72,73 Research has so far concentrated on treatments that can be easily applied to large technical surfaces and on PTFE, which has shown the lowest ice adhesion on flat surfaces, due to its low polarizability. The high polarity of water molecules means that induced dipoles are a major part of attachment forces on non-polar surfaces.…”
Section: Ice Resistancementioning
confidence: 99%
“…Th e contents extend from a new processing route for surfaces to droplet behavior on the surface, including sliding [6,9,32-34], freezing [35][36][37], evaporation [25,[38][39][40] and bouncing [41][42][43]. However, such surfaces have not been put into practical use except in very limited cases.…”
Section: Superhydrophobic Surfacesmentioning
confidence: 99%